The design and development of a serious game to introduce LIS concepts - Calceta, Anne Frances B.
Digital native students are known to learn better when presented with knowledge through familiar media, like video games. Because of that, serious games, which are games with a goal other than entertainment, can be used in introducing LIS concepts to digital natives. However, there is a fear of wasted effort in the creation of serious games due to the significant time and effort investment needed.